Insulin on the brain: The role of central insulin signalling in energy and glucose homeostasis. (9th March 2021) - Beddows, Cait A.; Dodd, Garron T.
Abstract: Insulin signals to the brain where it coordinates multiple physiological processes underlying energy and glucose homeostasis. This review explores where and how insulin interacts within the brain parenchyma, how brain insulin signalling functions to coordinate energy and glucose homeostasis and how this contributes to the pathogenesis of metabolic disease. Abstract : Insulin signals to the brain where it coordinates energy and glucose homeostasis. This review explores where and how insulin interacts within the brain, the role of brain insulin signalling in coordinating metabolism, and how this goes awry to contribute to the pathogenesis of metabolic disease.